Suppression of Endoplasmic Reticulum Stress by 4-PBA Protects Against Hyperoxia-Induced Acute Lung Injury via Up-Regulating Claudin-4 Expression - Pao, Hsin-Ping; Liao, Wen-I.; Tang, Shih-En; Wu, Shu-Yu; Huang, Kun-Lun; Chu, Shi-Jye (Frontiers in Immunology, 2021)
Endoplasmic reticulum (ER) stress that disrupts ER function can occur in response to a wide variety of cellular stress factors leads to the accumulation of unfolded and misfolded proteins in the ER. Many studies have shown that ER stress amplified inflammatory reactions and was involved in various inflammatory diseases. However, little is known regarding the role of ER stress in hyperoxia-induced acute lung injury (HALI). This study investigated the influence of ER stress inhibitor, 4-phenyl butyric acid (4-PBA), in mice with HALI. Treatment with 4-PBA in the hyperoxia groups significantly prolonged the survival, decreased lung edema, and reduced the levels of inflammatory mediators, lactate dehydrogenase, and protein in bronchoalveolar lavage fluid, and increased claudin-4 protein expression in lung tissue. Moreover, 4-PBA reduced the ER stress-related protein expression, NF-B activation, and apoptosis in the lung tissue. In in vitro study, 4-PBA also exerted a similar effect in hyperoxia-exposed mouse lung epithelial cells (MLE-12). However, when claudin-4 siRNA was administrated in mice and MLE-12 cells, the protective effect of 4-PBA was abrogated. These results suggested that 4-PBA protected against hyperoxia-induced ALI via enhancing claudin-4 expression.